Gasotransmitters in Gametogenesis and Early Development: Holy Trinity for Assisted Reproductive Technology-A Review - Nevoral, Jan; Bodart, Jean-Francois; Petr, Jaroslav (Oxidative medicine and cellular longevity, 2016)
Creation of both gametes, sperm and oocyte, and their fusion during fertilization are essential step for beginning of life. Although molecular mechanisms regulating gametogenesis, fertilization, and early embryonic development are still subjected to intensive study, a lot of phenomena remain unclear. Based on our best knowledge and own results, we consider gasotransmitters to be essential for various signalisation in oocytes and embryos. In accordance with nitric oxide (NO) and hydrogen sulfide (H2S) physiological necessity, their involvement during oocyte maturation and regulative role in fertilization followed by embryonic development have been described. During these processes, NO- and H2S-derived posttranslational modifications represent the main mode of their regulative effect. While NO represent the most understood gasotransmitter and H2S is still intensively studied gasotransmitter, appreciation of carbon monoxide (CO) role in reproduction is still missing. Overall understanding of gasotransmitters including their interaction is promising for reproductive medicine and assisted reproductive technologies (ART), because these approaches contend with failure of in vitro assisted reproduction.
Keywords: mužské pohlaví; Male; Carbon Monoxide; Humans; Female; gasotransmitery; lidé; asistovaná reprodukce; ženské pohlaví; oxid dusnatý; Reproductive Techniques, Assisted; Gametogenesis; oocyty; Hydrogen Sulfide; Animals; Oocytes; zvířata; gametogeneze; oxid uhelnatý; Nitric Oxide; sulfan; posttranslační úpravy proteinů; Protein Processing, Post-Translational; Gasotransmitters